Deixis in Folklore Collections and Implications for Learning Indonesian Language and Literature in Senior High School - Siti Setiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
In ten collections of folklore, the singular first person deixis appears most often in story II (Sawunggaling), while the plural first person deixis occurs most frequently in story III (The Faithfulness of a Wife). The total number of singular first person deixis is 86, while the plural first person deixis is 4. Furthermore, the second singular persona deixis appears most often in story II (Sawunggaling), while the second plural persona deixis appears most often in story II (Sawunggaling). The total number of singular second persona deixis in the story is 60 pieces, while the second plural persona deixis is 3 pieces. Then the singular third person deixis appears the most in story IV (The Game of Calamity), while the third person plural deixis appears the most in story X (Fire Stone). The total number of singular third person deixis in the story is 408, while the plural third person deixis is 95. Spatial deixis appears most often in story II (Sawunggaling). The total number of spatial deixis in the story is 84 pieces. Finally, time deixis, out of 10 folklore discourse deixis, time deixis appears the most in story III (The Faithfulness of a Wife). So of the three types of deixis, namely persona, space, and time deixis, only the second-plural persona deixis is very rarely found in stories. This means that the use of the second plural person deixis is rarely used in sentences.